2019
DOI: 10.1002/smll.201902220
|View full text |Cite
|
Sign up to set email alerts
|

A Co‐Doped MnO2 Catalyst for Li‐CO2 Batteries with Low Overpotential and Ultrahigh Cyclability

Abstract: energy density and good cycle stability is believed as a promising strategy to solve this issue. For example, Li-CO 2 batteries which have been developed on the basis of Li-O 2 batteries have recently attracted attention. This battery system not only offers a high energy density for electrochemical energy storage but also alleviates the greenhouse effect by capturing CO 2 . [5] More recently, Li-CO 2 batteries have been attempted as new energy carriers to store renewable energy, in which Li 2 CO 3 is the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 28 publications
0
68
0
Order By: Relevance
“…Ge et al reported on Co-doped α-MnO 2 nanowires used as catalysts for Li-CO 2 batteries. [13] α-MnO 2 interstitial sites were successfully doped with Co, whose concentration directly impacted electronic conductivity where the bandgap was shortened and an impurity band was formed in α-MnO 2 . Enhanced electrical transport and optimized hierarchical channel structures enable Co-doped α-MnO 2 catalysts to exhibit a high capacity of 8160 mA h g −1 , a low overpotential of about 0.73 V, and long cycle life of >500 cycles at 100 mA g −1 .…”
Section: Enhancing Electrical Transportmentioning
confidence: 99%
“…Ge et al reported on Co-doped α-MnO 2 nanowires used as catalysts for Li-CO 2 batteries. [13] α-MnO 2 interstitial sites were successfully doped with Co, whose concentration directly impacted electronic conductivity where the bandgap was shortened and an impurity band was formed in α-MnO 2 . Enhanced electrical transport and optimized hierarchical channel structures enable Co-doped α-MnO 2 catalysts to exhibit a high capacity of 8160 mA h g −1 , a low overpotential of about 0.73 V, and long cycle life of >500 cycles at 100 mA g −1 .…”
Section: Enhancing Electrical Transportmentioning
confidence: 99%
“…For the Lirich layered cathodes, EELS has been applied to investigate the injection of the oxygen vacancies into the bulk lattice, which is responsible for the layered-to-spinel phase transformation. [53b] Ex situ EELS has also been utilized to identify the transition products in the charge-discharge process of the metal-gas batteries, such as the Li-O 2 , [55] Li-CO 2 , [56] Na-CO 2 , [57] Li-CO 2 / O 2 , [58] Na-O 2 , [59] Na-N 2 , [60] etc. Combing the environmental TEM and the probe-type electrochemical solid-state open cell, Huang and co-workers conducted the first in situ TEM/EELS study of a Na-O 2 battery (Figure 6b).…”
Section: Intermediate State Characterizationsmentioning
confidence: 99%
“…The superior performance of the Co/α-MnO 2 composite was ascribed to the Co interstitial doping (Figure 11b) and highly conductive hierarchical channels of the MnO 2 NW network. [105] A CNT-supported MnO 2 composite has also been demonstrated as an efficient cathode catalyst in Li-CO 2 cells. [106] The electrochemical performance of Li-CO 2 cells with the MnO 2 /CNT catalyst is comparable with other types of Mn-based catalysts.…”
Section: Nonprecious Transition Metal-based Catalystsmentioning
confidence: 99%